Paying zakat to asnaf outside Malaysia/outside the state of the place of work / Aida Khairani Zaidi … [et al.] - Zaidi, Aida Khairani; Yusri, Atikah Nabilah; Mohd Fauzi, Nur Athirah; Mohd Jalani, Nursolehah; Hashim, Rohani (2023)
Zakat is one of the most fundamental pillars of Islam. It is an act of worship that is based on the principles of generosity, compassion, and social justice. Zak.at is the fourth pillar of Islam and is obligatory for every financially capable Muslim. The literal meaning of the word zakat is 'to cleanse,' Muslims believe that paying Zak.at purifies, increases, and blesses the remainder of their wealth. The act of zakat involves the giving of a portion of one's wealth to those in need. The practice of zakat is deeply rooted in the teachings of the Quran and the Sunnah of the Prophet Muhammad. It is one of the most important ways in which a Muslim can purify their wealth and attain spiritual growth. In the Qur'an, Allah has mentioned this act of worship thirty times, among them in Surah Al-Baqarah verse 43. "And establish prayer and give zakat and bow with those who bow [in worship and obedience]. "